2004
DOI: 10.1001/archneur.61.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Progression and Genetic Analysis in Hereditary Spastic Paraplegia With Thin Corpus Callosum in Spastic Gait Gene 11 (SPG11)

Abstract: Progressive axonal degeneration occurs in the corticocortical projections, corticospinal tract, and peripheral nerves in HSP with thin CC linking to chromosome 15q13-15 in a German pedigree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
55
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 20 publications
10
55
0
Order By: Relevance
“…Our data point toward distinct temporal functions of spatacsin, causing axonal transport deficits in corticospinal projections in mature neurons in vitro, and most likely during adulthood, in patients 12. It is imperative to speculate that the cortical changes (TCC and cortical atrophy) in SPG11 patients, when they first present with spastic paraplegia, are rather the results of defects in proliferation during cortical development,5, 6, 7 thereby highlighting a novel role for spatacsin in early neural development. Our current model of SPG11 disease pathology starts with an early‐onset neurodevelopmental phenotype (first two decades), consisting of a proliferation deficit and cortical neurogenesis defects.…”
Section: Discussionmentioning
confidence: 81%
“…Our data point toward distinct temporal functions of spatacsin, causing axonal transport deficits in corticospinal projections in mature neurons in vitro, and most likely during adulthood, in patients 12. It is imperative to speculate that the cortical changes (TCC and cortical atrophy) in SPG11 patients, when they first present with spastic paraplegia, are rather the results of defects in proliferation during cortical development,5, 6, 7 thereby highlighting a novel role for spatacsin in early neural development. Our current model of SPG11 disease pathology starts with an early‐onset neurodevelopmental phenotype (first two decades), consisting of a proliferation deficit and cortical neurogenesis defects.…”
Section: Discussionmentioning
confidence: 81%
“…31 A longitudinal clinical and neuroradiologic follow-up demonstrated further decrease of relative cerebral blood flow in the thalamus or cerebral cortex suggestive of progressive thalamic and cerebral cortical involvement. 21,32 At the level of the spinal cord, studies by Sperfeld et al 33,34 showed significant atrophy of the upper spinal cord in patients with HSP compared with the controls, both at the cervical and thoracic levels.…”
Section: Discussionmentioning
confidence: 97%
“…There are several reports in the literature of white matter hyperintensities (diffuse or patchy) and corpus callosum abnormalities in association with HSP. 9,10,17,19,20,[26][27][28][29][30] Thinning of the cervical and thoracic spinal cord has been noted in HSP. 31 Volume loss is an expected finding as there is a degeneration of the longer corticospinal tracts to the spinal cord (mainly to the lower limbs) and dorsal column pathway within the spinal cord.…”
Section: Discussionmentioning
confidence: 99%